The Effect of the Covid-19 Pandemic on MSME Income in Serang City - Muhamad Wahyudin (PT FORMOSA CENDEKIA GLOBAL, 2022)
The research uses a simple linear regression analysis method where the influence of the Covid-19 pandemic on MSME income is displayed in the form of a regression equation. And testing the hypothesis on the Covid-19 pandemic based on the t test tested the significance of the coefficient of variable X, obtained a t value of 7.269 with a significance level of 5% and df = 100-1 = 99, it is known that the t table value is 1.666 because t count (7.269 > 1.666) then H0 is rejected. The results of the study show that the magnitude of the influence of the Covid-19 pandemic on MSME income has an effect of 65.0%, while the other 35.0% is influenced by other factors. This is proven by the results of a sig value of 0.000 <0.05 and a positive regression coefficient value of 0.508 or 50.8% so that it can be concluded that for every increase in Covid-19 by 1%, MSME income will decrease by 50.8%